Modularity for the future in space robotics: A review. (December 2021) - Post, Mark A.; Yan, Xiu-Tian; Letier, Pierre
Abstract: This paper presents a review of modular and reconfigurable space robot systems intended for use in orbital and planetary applications. Modular autonomous robotic systems promise to be efficient, versatile, and resilient compared with conventional and monolithic robots, and have the potential to outperform traditional systems with a fixed morphology when carrying out tasks that require a high level of flexibility. Based on a set of fundamental concepts in modular self-reconfiguring robotics, advances in applying modular self-organizing robotics technologies to aerospace applications and space mission concepts are summarized for the purpose of identifying relevant requirements and solutions. Based on this survey, critical guidelines for the implementation of in space assembly and operation using modular autonomous robotic systems are identified. Highlights: Modular & reconfigurable space robots have many advantages and practical challenges. A review of proposed modular systems and fundamental concepts for them are provided. A critical review of technologies highlights many system requirements & challenges. Key recommendations are made for implementation of modular robotic systems in space.